Implementation of the POGIL Model Combined with a Digital Mind Map Based on Online Learning to Improve Creative Thinking Skills and Student Cognitive Learning Outcomes at SMAN 2 Malang - Khorinah, Sheryl Afifatul; Susilo, Herawati; Balqis, Balqis - (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2023)
Education in 21st Century has supported use of the 2013 Curriculum which demands skills, one of which is creative thinking skills. This skill demand is inversely proportional to the real conditions in class XI MIPA 3 SMAN 2 Malang. Initially, creative thinking skills showed an average of 50.20%, indicated that student still had difficulty writing many different answers and were not equipped with details, used the language of books and the internet, did not see problems from various directions. Low cognitive learning outcomes are proven by the 2020/2021 odd semester exam scores with 41.39% of students getting scores below the KKM. Teachers have difficulty implementing learning models during the Covid-19 pandemic. The research aims to improve creative thinking skills and cognitive learning outcomes using the POGIL model combined with a digital mind map based on online learning. The research aims to improve students’ creative thinking skills and cognitive learning outcomes using POGIL model combined digital mind map based on online learning. The method uses Classroom Action Research with Kemmis & Mc Taggart design. Collecting data through creative thinking questions from UKBM, digital mind map, and pretest-posttest. The results of the cycle I and cycle II showed an increase in creative thinking skills from 78.37 to 86.26 (UKBM) and 83.74 to 91.50 (digital mind map), the average class cognitive learning outcomes from 78.90 to 80.29, and classical cognitive completeness by 80.65% to 87.10%. The increase was due to the integration of guided inquiry, cooperative, and digital mind map that we're able to create an active atmosphere, creative thinking, teamwork, and concept formation. DOI: http://dx.doi.org/10.23960/jbt.v11.i2.28827